2012
DOI: 10.2478/v10175-012-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Static axial crush performance of unfilled and foamed-filled composite tubes

Abstract: Abstract. The use and the combination of new, high efficient materials for crashworthiness is of great interest nowadays. Foamed materials are commonly used to increase efficiency of composite materials. Based on the results obtained by Brachos and Douglas, it can be concluded that the sum of the energy absorption capabilities of the foamed filling and unfilled composite tubes is smaller than the energy absorbed by the tubes filled with the same filling. The paper presents the results of the experimental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…These values are significantly higher than those observed in more traditional sandwich structures. For example, previous studies have reported SEA values of only up to 45 kJ/kg for aluminium honeycomb [34], 5.5 kJ/kg for aluminium foam [17] and 18 kJ/kg for Nomex honeycomb [34]. Finally, the values for the larger diameter tubes are relatively constant across the range of areal densities considered.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These values are significantly higher than those observed in more traditional sandwich structures. For example, previous studies have reported SEA values of only up to 45 kJ/kg for aluminium honeycomb [34], 5.5 kJ/kg for aluminium foam [17] and 18 kJ/kg for Nomex honeycomb [34]. Finally, the values for the larger diameter tubes are relatively constant across the range of areal densities considered.…”
Section: Resultsmentioning
confidence: 90%
“…A number of researchers [1317] have investigated the energy-absorbing characteristics of metal-based foams, such as those manufactured from aluminum alloys. The strain-rate sensitivity of closed-cell aluminium foam specimens in uniaxial compression was investigated by Paul and Ramamurty [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ochelski et al [57] analyzed the crushing potential of unfilled and elastomer-filled composite tubular structures. Ochelski et al [58] investigated the performance of unfilled and foam-filled fiber-reinforced tubes. Arbaoui et al [59] evaluated the influence of variations in core thickness and intermediate layers on the mechanical properties of a polypropylene honeycomb core.…”
Section: Recent Trends In Honeycomb Sandwich Compositesmentioning
confidence: 99%
“…A support pillar is made of I-beam and is loaded by weight of a sur-rounding roof structure, represented by the force P and the lumped mass M. The multilayer protective panel consists of steel, fibre reinforced composite and metallic foam. A choice of such a layout was partially driven by experimental results showing a very good crashworthiness of foam and composites assembled together [13]. It is assumed, that two different phenomena are responsible for minimization of shock wave effects: flow around cylindrical panel and energy absorption by a panel structure.…”
Section: Analysed Problemmentioning
confidence: 99%